An Assessment of the Libyan Oil and Gas Industry’s Adoption of International Financial Reporting Standards (IFRSs) - Alsekily , Ragab Abdelsalam Salim (Finance and Business Economies Review, 2023)
This research discusses the background of IFRS and how international organizations might help to promote the implementation of IFRS., and the progress of accounting. It discusses the pros and cons of adopting IFRS in industrialized countries. By focusing on Libya's decision to implement IFRS for its extractive industry, the study advances our understanding, a topic that has not before been investigated, and how to better comprehend the possible advantages and obstacles to IFRS adoption in developing countries. Also study aims to comprehend the variables, both internal and external influencing the sector transition to IFRS. The current assessment gave a general overview of the environment. Furthermore, the unions in accounting and groups that the previous government had established had no interest in advancing accounting standards and procedures because they were quite political in nature. As a result, accounting education and training programs were either inadequate or non-existent.